Sexual Assault as a Contributor to Academic Outcomes in University: A Systematic Review. (January 2023) - Molstad, Taylor D.; Weinhardt, Justin M.; Jones, Rihannon
Sexual assault continues to be a prevalent and consequential experience for university students. The aim of this systematic review was to synthesize the literature on the academic consequences of the sexual assault for university students. There is currently no comprehensive review of the literature focusing on the academic consequences for university students who experienced sexual assault. This review was conducted based on searches from five databases including Academic Search Complete, Education Search Complete, Education Resources Information Center (ERIC), PsycINFO, and Google Scholar. We identified 13 articles that examined academic consequences of sexual assault during university. Across all studies, sexual assault was associated with more academic problems including lower grade point average, dropping out of university, and self-regulated learning problems. Although the number of articles is small, the results are consistent. Practically, this means that universities, those providing psychological services, and victims themselves need to understand that the consequences are not just physical and psychological but can also negatively impact academic achievement. Our review also identifies limitations in the literature regarding this topic such as methodological concerns, diversity and inclusion concerns, and the need for future work to investigate mediators of the relationship between sexual assault and academic outcomes. We offer recommendations for future research to combat the concerns identified. Development of interventions to support those who experience sexual assault during university necessitates overcoming the limitations identified.